Understanding and learning statistics by computer - Yang, Mark C. K (World Scientific, 1986)
Bibliography: p. [183]-184; 8 chapters: Sampling by computer simulation; commonly used populations and their generation; the binomial distribution and its applicationto simulation; comparision of statistical procedures;...